Pengaruh Satisfaction, Variety Seeking Dan Alternative Attraction Terhadap Switching Behavior Melalui Switching Intentions - Julaiha, Siti; Sabran, Sabran; Ilham, Ilham (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
This research aims to test and analyze the influence of Satisfaction, Variety Seeking and Alternative Attraction on Switching Behavior through Switching Intentions. The research sample consisted of 75 people. Sampling used Non Probability Sampling techniques and data analysis tools using Structural Equation Modeling (SEM) using Smart PLS version 4 software. The results of the study showed that (1) Satisfaction had no effect on Switching Behavior (2) Variety Seeking had no effect on Switching Behavior ( 3) Alternative Attraction has an effect on Switching Behavior (4) Switching Intentions has no effect on Switching Behavior (5) Satisfaction has no effect on Switching Behavior through Switching Intentions (6) Variety Seeking has no effect on Switching Behavior through Switching Intentions (7) Alternative Attraction has no effect on Switching Behavior through Switching Intention.